Rural Environmental Concern: Effects of Position, Partisanship, and Place1. (16th September 2013) - Hamilton, Lawrence C.; Hartter, Joel; Safford, Thomas G.; Stevens, Forrest R.
Abstract The social bases of environmental concern in rural America resemble those for the nation as a whole, but also reflect the influence of place. Some general place characteristics, such as rates of population growth or resource‐industry employment, predict responses across a number of environmental issues. Other unique or distinctive aspects of local society and environment matter as well. We extend earlier work on both kinds of place effects, first by analyzing survey data from northeast Oregon. Results emphasize that "environmental concern" has several dimensions. Second, we contextualize the Oregon results using surveys from other regions. Analysis of an integrated dataset (up to 12, 000 interviews in 38 U.S. counties) shows effects from respondent characteristics and political views, and from county rates of population growth and resource‐based employment. There also are significant place‐to‐place variations that are not explained by variables in the models. To understand some of these we return to the local scale. In northeast Oregon, residents describe how perceptions of fire danger from unmanaged forest lands shape their response to the word conservation. Their local interpretation contrasts with more general and urban connotations of this term, underlining the importance of place for understanding rural environmental concern.